Investigating the Relationship between knowledge Management and Organizational Culture from the Viewpoint of the Academic Staff Members of Medical Sciences University of Kerman - Amin Nikpour; Sanjar Salajegheh (مدیریت بهره وری, 2010)
Knowledge is considered as the major resource of organizations and is acknowledged as an asset. Organizational culture is necessary for communication, creation and using knowledge, and universities as organizations that produce knowledge should possess this aspect. The purpose of this research is to determine the relationship between the knowledge management and the organizational culture. The statistical population involves all of the academic staff members of Medical Sciences University of Kerman, Which was 310 during the time of doing the research. Sampling was done by regular stratified method and included the academic members of different fields and departments, from among whom 70 people were chosen based on Morgan’s table. In order to collect information, the questionnaires about organizational culture and management of knowledge were used. Descriptive and inferential statistics (correlational coefficient and x2) were used to analyze the data. The results of this descriptive research that has been done by the survey   method  show that there is a positive correlation between knowledge management and organizational culture. The findings of the research show that organizational mission has the highest correlational coefficient and the creation of knowledge has the least correlational coefficient